CODE-MIXING ANALYSIS IN THE NOVEL A VERY YUPPY WEDDING - Aswarini Sentana (Journal of Language and Literature, 2022)
This sociolinguistic research analyzes code-mixing occurrences in the Indonesian novel entitled A Very Yuppy Wedding. This research aims to find (1) the types of code-mixing and (2) the factors influencing code-mixing in the studied novel. The method used in this research is a descriptive qualitative method through library research. The results show that the types of code-mixing in the conversation within the novel are insertion, alteration, and congruent lexicalization. Meanwhile, the factors influencing code-mixing done by the characters in the novel are (1) participant roles and relationships, (2) situational factors, (3) message intrinsic factors, and (4) language attitudes, dominance, and security. This research finds that insertion code-mixing dominates the types of code-mixing found in the novel. The characters in the novel often insert an English word or phrase into their utterance, which is in the Indonesian Language, especially when they talk to their coworkers. The characters also tend to mix their Language depending on situational factors such as settings and topics of discourse. For example, they will insert English words or phrases to discuss business and sports.